Enhancing Tef Growth and Yield through Integrated Application of Plant Growth-Promoting Rhizobacteria and Reduced Chemical Fertilizers - Zerihun Tsegaye; Tesfaye Tamiru (Journal of Genetic Resources, 2025)
Tef is a staple crop in Ethiopia, serving as the primary food source for approximately 70 million people and contributing significantly to the country's agricultural economy. Its high protein content, gluten-free nature, and rich micronutrient profile make it nutritionally vital for populations with dietary restrictions like celiac disease. This study evaluates the synergistic effects of stress-tolerant plant growth-promoting rhizobacteria (PGPR) and reduced chemical fertilizers on tef to enhance growth parameters, yield components, and nutrient content. The experiment was conducted using a completely randomized design with three replications. Stress-tolerant PGPR was applied individually and in consortium with half the recommended dose of chemical fertilizers at the seeding and flowering stages to facilitate effective root colonization and growth. Variance analysis revealed significant improvements in various growth and yield parameters of the Dukem tef variety (Dz-01-974) due to the integrated application of the PGPR consortium and reduced chemical fertilizers increased grain yield per plant by 32% (5.25 g vs 3.98 g control; P< 0.01) and shoot dry weight by 28% (10.4 g vs 8.1 g control; P< 0.01). Additionally, the grain nutrient content significantly (p< 0.05) improved, with phosphate at 3.83%, nitrogen at 1.99%, and calcium at 0.18% over the control. Integrating PGPR with reduced chemical fertilizers offers a promising strategy for improving tef growth and yield, as well as reducing dependency on chemical inputs. This approach has the potential to promote more sustainable agricultural practices, improve the nutritional content of tef, and lower production costs for farmers. Further long-term studies are necessary to validate these findings and explore the broader implications for soil health and crop productivity.